Online Technology for Occupational Therapy: blazing a new highway for the way we are ALL going to travel in the next era. Issue 1 (May 2014) - Hook, Angela; Bodell, Sarah; Hamilton, Anita; Penman, Merrolee; Burwash, Susan; Jacobs, Karen
Abstract : Online Technology for Occupational Therapists (OT4OT) has been an established group of volunteers since 2010. We are now into the 4th year of delivery of the 24-hour virtual knowledge exchange for occupational therapists (OT24Vx). By using technology to engage in knowledge brokering we have reached over 1000 participants in 30 countries, thereby blazing a new highway for the way we are ALL going to travel in the next era and fostering a sense of unity across the world of the commitment to occupation and enthusiasm for our profession. This paper presents an account of the development of OT4OT and its mission in relation to knowledge brokering and global professional development.